Analisis Gaya Kepemimpinan Demokratis dalam Meningkatkan Motivasi Anggota Organisasi Himpunan Mahasiswa Prodi Manajemen UNUSIDA - Naswa Ika Febrianty; Wahyu Eko Pujianto (JURNAL RISET MANAJEMEN (JURMA), 2024)
Democratic leadership is a leader who makes decisions by involving the participation of members in an organization and decisions taken after reaching a mutual agreement. The research conducted aims to find out whether the leadership carried out is democratic and whether democratic leadership can increase the motivation of members of the Management Study Program Student Association organization. The research was conducted using qualitative methods using data collected in the form of observations and interviews with members of the Management Study Program Student Association organization, both active, passive, and proactive members. The results of the research that have been carried out are the leadership of the Management Study Program Student Association carried out by democratic leadership which is interrelated with its members through two categories including communication and decision making. Democratic leadership affects the motivation of organizational members because it can make members comfortable to organize and members can work with loyalty to the Management Study Program Student Association organization.